ONTOLOGINIS SEKSUALINĖS SKIRTIES ASPEKTAS L. IRIGARAY FILOSOFIJOJE. - Dovydėnas, Andrius (Problems / Problemos, 2016)
The article analyses the transformation of the conception of sexual difference in the philosophy of Luce Irigaray. The controversy between essentialism and constructivism in philosophy of gender is the context of the analysed question and it is used as a heuristic scheme in this article. Taking into consideration this context, it is asserted that the early Irigaray's psychoanalytic conception of sexual difference and the mimesis as a means to constitute feminine subjectivity correspond only to political or "strategic essentialism". Meanwhile, in her transformative point of philosophy, in contesting Hegel's paradigm of the subject, Irigaray present a naturalistic conception of sexual difference, which already implies the ontological essentialism. Also the analysis includes the principle of genus identity in the philosophy of Hegel which had rested unexamined by Irigaray. The aim is not only to reveal the concept of Irigaray's feminine subjectivity, which comprises the irreducibility of femininity into a function of reproduction, the incommensurability of masculine and feminine subjectivities, but also to highlight the controversy of sexual difference and genus identity as two different paradigms of philosophy of the subject.